PENGUATAN KEPEMIMPINAN TRANSFORMASIONAL, BUDAYA ORGANISASI, KREATIVITAS GURU DALAM UPAYA MENINGKATKAN KEINOVATIFAN GURU - Fauzi, Ahmad; Hardhienata, Soewarto; Irdiyansyah, Iyan (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
This research aims to find strategies and ways to increase the innovativeness of state madrasah tsanawiyah teachers through strengthening transformational leadership, organizational culture and teacher creativity. The research uses the path analysis method and SITOREM analysis with a quantitative approach. The research population was 178 people and the sample was calculated using the Slovin formula as 123 state Tsanawiyah madrasah school teachers. The statistical tests involved in this research include preliminary tests, hypothesis testing with path analysis, correlation tests and coefficient of determination tests. For indicator analysis, use SITOREM analysis. The research results show that there is a direct positive influence: (1) transformational leadership on teacher innovativeness (βy1=0.262); (2) organizational culture on teacher innovativeness (βy2=0.225); (3) teacher creativity towards teacher innovativeness (βy3=0.441); (4) transformational leadership on teacher creativity (βx13=0.534); (5) organizational culture on teacher creativity (βx23=0.399); (6) There is an indirect positive influence of transformational leadership on teacher innovativeness through teacher creativity, Zcount value (6.187); (7) positive indirect organizational culture on teacher innovativeness through teacher creativity, Zcount value (6.814). This research concludes that strengthening transformational leadership, organizational culture and teacher creativity can increase teacher innovativeness, especially in Madrasah Tsanawiyah Negeri Bogor Regency.